Lancemaside A from Codonopsis lanceolata prevents hypertension by inhibiting NADPH oxidase 2-mediated MAPK signalling and improving NO bioavailability in rats. (26th July 2019) - Shin, You Kyoung; Han, A Young; Hsieh, Yu Shan; Kwon, Soonho; Kim, Jinhye; Lee, Kwang-Won; Seol, Geun Hee
Abstract: Objectives: This study investigated whether lancemaside A (LMA) can prevent hypertension and assessed the mechanisms of action of LMA in rats. Methods: Hypertension was induced by chronic immobilization stress and nicotine administration. Hypertensive vehicle rats were treated with LMA (1, 20, or 40 mg/kg) or nifedipine (10 mg/kg) as a positive control daily for 3 weeks. Key findings: In hypertensive vehicle rats, LMA dose-dependently reduced systolic blood pressure. LMA doses of 20 and 40 mg/kg reduced the aortic expression of nicotinamide adenine dinucleotide phosphate oxidase (NOX)2 (both P < 0.01), and 40 mg/kg LMA reduced serum malondialdehyde ( P < 0.01). Serum nitrite levels were significantly higher in LMA treated rats than in hypertensive vehicle rats, with LMA doses of 20 and 40 mg/kg reducing the expression of endothelial nitric oxide synthase in rat aortas ( P < 0.001 and P < 0.01, respectively). LMA also reduced the aortic levels of nuclear factor kappa B and the activation of the three isoforms of mitogen-activated protein kinase (MAPK). Conclusions: Lancemaside A prevents hypertension in rats by inhibiting the activation of MAPK signalling and the impairment in nitric oxide bioavailability due to NOX2-mediated oxidative stress. Thus, LMA may act as a preventive agent for hypertension.